Growth-Oriented Adjustment. Programs Conceptual Framework (IMF Working Papers, 1988)
This paper suggests a conceptual framework that can serve as a basis for the design of growth-oriented adjustment programs. The two building blocks of the model are the well-known monetary approach to the balance of payments, and a variant of the open-economy neoclassical growth model. The integrated model combines growth, inflation, and the balance of payments, and links these objectives to government policies and the availability of foreign financing. The principal advantage of the proposed framework is its simplicity, which enables it to be applied relatively easily to a variety of developing countries